Inequality and the Status Window: Inequality, Conflict, and the Salience of Status Differences in Conflicts over Resources - Kevin T. Leicht (RSF: The Russell Sage Foundation Journal of the Social Sciences, 2022)
The study of the relationship between social status and inequality has a distinguished history. Inequality scholars outside this tradition have paid more attention to social status in response to a set of seemingly persistent paradoxes that defy easy explanation. I add to the tradition by developing the concept of status windows and status windows overlap to partially account for differences in the relationship between social status and inequality processes in low- and high-inequality environments. These concepts are tied to the functioning of social status in creating and maintaining inequality and to the characteristics of social networks that develop in (especially) high-inequality environments. I examine how the concepts of status windows and status window overlap can help explain some paradoxes in responses to heightened social inequality and recommend that research focus on understandings of status windows and status windows overlap to understand why social inequality continues unabated in some places.